Analisis Faktor Penyebab CCO dan Pengaruhnya Terhadap Biaya Kontraktor Pada Proyek Jalan Tol - Zen Tenno; Agus Suroso (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2021)
This case study showed a 54% increase in Contract Change Order (CCO) work against the initial contract fee. The purpose of this study was to determine the factors that cause the occurrence of CCO, the influence of CCO on the contractor cost performance, and how much CCO affecting the contractor costs performance on toll road projects. The research method was using survey methods and data are processed with multiple linear regression. The results of this research shows that CCO work has the impact of increasing costs because of several factors such as contract documents, stakeholders, design, and construction. The most dominant variables that increase in costs were construction variables with a test value of 2,830, a significant value of 0.007, and a regression coefficient of 0.103. This research greatly influenced the performance of costs on toll road works by 80.9% of the remaining 19.1% described by other variables beyond the regression model analyzed.